Menyoal Peran Panitia Pengawas Pemilu Dalam Pilkada - Zainuddin . (Universitas Negeri Gorontalo, 2009)
Election of Regional leader and Deputy Of Area directly has given new nuance of indonesia politics as presentation of return of democracy at local public. Quality and democratic process of Pilkada Implementation hardly determined by readiness of local government and election organizer. Panwaslu as the one and only supervisor of the election that entrusted by local government Law and the Low of the election implementation that observe all step of Pilkada implementation must be independently in their job and authorities Kata Kunci : Peran. Panwaslu. Pemilu. dan Pilkada. Otonomi Daerah